2019
DOI: 10.1016/j.bcp.2018.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome biogenesis: An emerging druggable pathway for cancer therapeutics

Abstract: Ribosomes are nanomachines essential for protein production in all living cells. Ribosome synthesis increases in cancer cells to cope with a rise in protein synthesis and sustain unrestricted growth. This increase in ribosome biogenesis is reflected by severe morphological alterations of the nucleolus, the cell compartment where the initial steps of ribosome biogenesis take place. Ribosome biogenesis has recently emerged as an effective target in cancer therapy, and several compounds that inhibit ribosome prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
99
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 97 publications
(161 reference statements)
1
99
0
2
Order By: Relevance
“…Ribosomes are associated with bone marrow failure, skeletal and other developmental abnormalities, immune signaling, and cancer predisposition, 27‐30 and are overexpressed in several cancers such as hepatocellular cancer and gastric cancer 31,32 . Moreover, downregulation of ribosomal proteins reportedly suppresses tumorigenesis and progression, 33 suggesting that ribosomes constitute a potential target for cancer treatment 34,35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribosomes are associated with bone marrow failure, skeletal and other developmental abnormalities, immune signaling, and cancer predisposition, 27‐30 and are overexpressed in several cancers such as hepatocellular cancer and gastric cancer 31,32 . Moreover, downregulation of ribosomal proteins reportedly suppresses tumorigenesis and progression, 33 suggesting that ribosomes constitute a potential target for cancer treatment 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…The nucleolus is larger in malignant than in not‐malignant cancer cells 33 . A recent study reported that translation of rRNA and nucleolar regulation promote glioma tumorigenesis 33‐35,38 …”
Section: Discussionmentioning
confidence: 99%
“…The development of optogenetic approaches to engineer the assembly of de novo condensates (25)(26)(27)(28), and now to modulate the properties of endogenous ones, promises to have an enormous impact on our understanding of these emerging links between the material properties and (dys)function of the nucleolus. These insights will suggest new therapeutic approaches for tackling ribosome disorders by modulating nucleolar assembly and material properties, adding novel options to the developing arsenal targeting the nucleolus for anticancer intervention (54).…”
Section: Discussionmentioning
confidence: 99%
“…A lack of proper ribosome biogenesis is associated with the production of free RPs, a prototype being ribosomal protein uL5, that then interacts with HDM2/MDM2, interfering with its function to degrade p53, preventing a tumor-suppressive response [54,55]. Ribosome biogenesis is therefore considered as an attractive anti-cancer target [56]. As a matter of fact, it has been realized that interference with ribosome biogenesis was part of the anti-cancer properties of several classic anti-neoplastic drugs, even if the ribosome was not considered as their primary target [57].…”
Section: Targeting Ribosome Biogenesismentioning
confidence: 99%